2020
DOI: 10.1155/2020/3858373
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Signature Based on Autophagy‐Associated LncRNAs for Predicting Prognosis in Lung Adenocarcinoma

Abstract: Objective. To construct a predictive signature based on autophagy-associated lncRNAs for predicting prognosis in lung adenocarcinoma (LUAD). Materials and Methods. Differentially expressed autophagy genes (DEAGs) and differentially expressed lncRNAs (DElncRNAs) were screened between normal and LUAD samples at thresholds of ∣log2Fold Change∣>1 and P value < 0.05. Univariate Cox regression analysis was conducted to identify overall survival- (OS-) associated DElncRNAs. The total cohort was randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
(31 reference statements)
0
13
0
Order By: Relevance
“…We compared the performance for OS prediction of 7-FIRLs signature (hereinafter referred to as LncSig) and other published prognostic signatures [ 15 , 34 , 35 ]: the lncRNAs signature derived from Zhang’s study (ZhangLncSig), Zhou’s study (ZhouLncSig) and Jin’s study (JinLncSig). Utilizing the same TCGA patient cohort, risk scores of each signature were calculated based on normalized expression values and coefficients provided by original articles and ROC analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the performance for OS prediction of 7-FIRLs signature (hereinafter referred to as LncSig) and other published prognostic signatures [ 15 , 34 , 35 ]: the lncRNAs signature derived from Zhang’s study (ZhangLncSig), Zhou’s study (ZhouLncSig) and Jin’s study (JinLncSig). Utilizing the same TCGA patient cohort, risk scores of each signature were calculated based on normalized expression values and coefficients provided by original articles and ROC analysis was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we also carried out a predictability comparison between GInLncSig and four recently reported lncRNA signatures using the same patients cohort of TCGA for survival prediction of patients with LUAD: thirteen-lncRNA prognostic signature reported by Zhou et al (2020) (ZhoulncSig), five-lncRNA prognostic signature reported by Zeng et al (2019) (ZenglncSig), five-lncRNA prognostic signature documented by Liao et al (2018) (LiaolncSig), and the seven-lncRNA prognostic signature reported by Jin et al (2020) (JinlncSig). As is depicted in Figure 6E , our GInLncSig with an AUC of ROC for the 1-year OS of 0.739 was more effective in predicting patients’ survival than ZhoulncSig (AUC = 0.656), ZenglncSig (AUC = 0.639), LiaolncSig (AUC = 0.649), and JinlncSig (AUC = 0.655).…”
Section: Resultsmentioning
confidence: 99%
“…AL034397.3 was found to be correlated with autophagy in LUAD. However, the specific function and mechanism have not been reported ( Zhou et al, 2020 ). DENG et al found that the expression of CHOD1-AS1, in low-grade gliomas, was at the lower level.…”
Section: Discussionmentioning
confidence: 99%